The Death Penalty Between International Guarantees and Moroccan Law - Ezzohra El hajraoui, Fatima; Ed-daran, Driss (Advances in Social Sciences Research Journal, 2015)
Abstract: For as long as the human right to life was the main goal of an international community, a number of global conventions and regional and international resolutions were aimed at reducing the death penalty. However, this does not mean that the death penalty and retribution in the Arab countries (Islamic Countries) were abolished; they were and still are a black point that stands in front of this right. In many parts of the world, the death penalty is now understood to be a human rights violation. This understanding has led to progress in the abolition of the death penalty in almost all the countries. Countries which have not abolished the death penalty can execution it only for the most serious crimes and issued pursuant to a final judgment of a competent court, with the possibility of Pardon or commutation of sentence. There are limitations to practice the death penalty, like application of the death penalty for persons who not reach eighteen years of age. Examining the death penalty from a human rights perspective not only highlights the impact of denying the most basic right to all other rights but also demonstrates why the only “solution” to the death penalty is to permanently end its use. In this paper, we discuss the most important points in the death penalty, which is the evolution of the death penalty, considering international efforts to abolish capital punishment. Then, the safeguards guaranteeing protection of the rights of those facing the death penalty give us illustrations of some countries. Finally, we discuss the death penalty in the Moroccan law as one of the countries that did not recognize in their national laws to cancel the punishment, and did not work on it since 1993. This is without forgetting to give some suggestions on this subject.